Sustainable housing : LFEA of precast frame - Abd. Ghafar, Nor Hayati (2004)
Precast concrete structures is a system where parts, members, and elements of structures are produced in the factory, and transported to the construction site. The frame structure for single storey housing is the focus of this analysis. 'W' shape steel with 5 mm thickness and 480 N/mm2 strength is proposed to replace all reinforcement in the beam and column. Linear finite element analysis (LFEA) was carried out to predict the mode of failure using COSMOSIM software. The whole frame model is assumed as Solid elements that are connected to each other using nodes. The failure on the structures was based on principal stress PI, principal stress P3, and resultant displacement contour plot.